2021
DOI: 10.1111/1750-3841.15708
|View full text |Cite
|
Sign up to set email alerts
|

The interaction mechanism between liposome and whey protein: Effect of liposomal vesicles concentration

Abstract: The interaction mechanism between liposomes (Lips) and whey protein isolates (WPI) with different mass ratios was explored in this paper. After binding with different concentration of Lips, the changes in hydrophilic and hydrophobic regions of WPI were investigated with fluorescein isothiocyanate (FITC) and pyrene fluorescence probes. The spatial structure changes of WPI were further characterized by differential scanning calorimetry, Fourier transform infrared spectroscopy, and circular dichroism. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…What is more, this interaction reduced molecular chain mobility of nanoliposomes to compact and rigidize the structure 21 . The phenomenon was in line with prior studies, where the decomposition temperature of fucoidan coated nanoliposomes 59 and whey protein coated nanoliposomes 60 were higher than only nanoliposomes.…”
Section: Resultssupporting
confidence: 89%
“…What is more, this interaction reduced molecular chain mobility of nanoliposomes to compact and rigidize the structure 21 . The phenomenon was in line with prior studies, where the decomposition temperature of fucoidan coated nanoliposomes 59 and whey protein coated nanoliposomes 60 were higher than only nanoliposomes.…”
Section: Resultssupporting
confidence: 89%
“…Changes in the FTIR band shape, shift, or intensity indicate the occurrence of intermolecular interactions. Three polysaccharides, ALG, XG, and CMC, have characteristic bands at 3269.8, 3300.4, and 3335.9 cm –1 , respectively, which belong to the stretching vibration of hydroxyl (O–H) groups, stretching vibration peaks at 1592.8, 1602.8, and 1588.1 cm –1 assigned to carbonyl (CO) in carboxylate anion (COO – ), and C–O stretching bands at 1409.3, 1046.6, and 1414.5 cm –1 . For the WPIF-ALG, WPIF-XG, and WPIF-CMC composites, the O-H bands changed at 3273.5, 3273.3, and 3272.7 cm –1 , respectively, near those of WPIFs, which had a highly ordered hydrogen bond network, suggesting the formation of hydrogen bonds in the composites.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies showed that the combination of PS and NL can improve the physicochemical properties of NL (Fang et al ., 2020; Xu et al ., 2023). Whey protein (WP), a kind of protein extracted from milk, is extensively employed as a protein supplement and a functional additive in the food industry (Chen et al ., 2021). WP with a large number of charged groups is more water‐soluble and less likely to cause allergic reactions compared to other commonly used proteins (such as ovalbumin and soy protein isolate).…”
Section: Introductionmentioning
confidence: 99%